2002
DOI: 10.1007/s00268-001-0267-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the presence of hepatitis B e antigen on prognosis after liver resection for hepatocellular carcinoma in patients with chronic hepatitis B

Abstract: We examineded the clinical effects of serum hepatitis B e antigen (HBeAg) positivity on clinicopathologic findings and prognosis after liver resection for hepatocellular carcinoma (HCC) in patients with chronic hepatitis B. A series of 56 patients who underwent curative resection were divided into two groups: 25 HBeAg-positive patients (group 1) and 31 HBeAg-negative patients (group 2). The mean age was significantly lower in group 1 than in group 2 (p = 0.0021), and the proportion of patients with symptoms wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 46 publications
3
25
0
Order By: Relevance
“…36,37 Patients in the immuneclearance phase of chronic hepatitis B infection are at high risk of HCC recurrence after the operation. In this study, only group A included such patients, which explains why chronic hepatitis B status, tumor factors, and the type of operation affected recurrence, whereas in group B only tumor factors affected recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Patients in the immuneclearance phase of chronic hepatitis B infection are at high risk of HCC recurrence after the operation. In this study, only group A included such patients, which explains why chronic hepatitis B status, tumor factors, and the type of operation affected recurrence, whereas in group B only tumor factors affected recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…There have been only a few reports on outcomes after hepatectomy for small HCC in relation to the HB envelope [6,7]. In the present study, favorable long-term surgical outcomes were achieved in patients with HBV-related HCC within the Milan criteria and positive HBe-Ab.…”
Section: Discussionmentioning
confidence: 47%
“…Therefore, the higher carcinogenesis of HCC or poorer prognosis in patients who are positive for HBe-Ag than in patients who are negative for HBe-Ag has been reported [1]. Furthermore, poorer surgical outcomes after hepatectomy for small HCC in patients who are positive for HBe-Ag than in patients who are negative for HBe-Ag have been reported [6,7] However, there have been no previous reports of surgical outcomes of HCC within Milan criteria in relation to the HB envelope. In this study, lower risk of recurrence and longer survival were seen in patients who were positive for HBe-Ab than in patients who were negative for HBe-Ab.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As mentioned above, because viral replication reflected as sustained HBeAg positivity and a high viral load adversely affects the development of HCC, it is reasonable to suggest that viral replication may also facilitate de novorecurrence in the remnant liver. Several studies support this hypothesis, but the detailed effects of viral replication on recurrence differ somewhat among studies [52,53,54,55,56,57,58]. Sun et al [56] reported that a positive serum HBeAg was associated with a higher risk of early recurrence (within 1 year) rather than late recurrence.…”
Section: Tertiary Preventionmentioning
confidence: 72%